What do health professionals need to know about young onset dementia? An international Delphi consensus study - Leah Couzner; Sally Day; Brian Draper; Adrienne Withall; Kate E. Laver; Claire Eccleston; Kate-Ellen Elliott; Fran McInerney; Monica Cations (BMC, 2022)
Abstract Background People with young onset dementia (YOD) have unique needs and experiences, requiring care and support that is timely, appropriate and accessible. This relies on health professionals possessing sufficient knowledge about YOD. This study aims to establish a consensus among YOD experts about the information that is essential for health professionals to know about YOD. Methods An international Delphi study was conducted using an online survey platform with a panel of experts (n = 19) on YOD. In round 1 the panel individually responded to open-ended questions about key facts that are essential for health professionals to understand about YOD. In rounds 2 and 3, the panel individually rated the collated responses in terms of their importance in addition to selected items from the Dementia Knowledge Assessment Scale. The consensus level reached for each statement was calculated using the median, interquartile range and percentage of panel members who rated the statement at the highest level of importance. Results The panel of experts were mostly current or retired clinicians (57%, n = 16). Their roles included neurologist, psychiatrist and neuropsychiatrist, psychologist, neuropsychologist and geropsychologist, physician, social worker and nurse practitioner. The remaining respondents had backgrounds in academia, advocacy, or other areas such as law, administration, homecare or were unemployed. The panel reached a high to very high consensus on 42 (72%) statements that they considered to be important for health professionals to know when providing care and services to people with YOD and their support persons. Importantly the panel agreed that health professionals should be aware that people with YOD require age-appropriate care programs and accommodation options that take a whole-family approach. In terms of identifying YOD, the panel agreed that it was important for health professionals to know that YOD is aetiologically diverse, distinct from a mental illness, and has a combination of genetic and non-genetic contributing factors. The panel highlighted the importance of health professionals understanding the need for specialised, multidisciplinary services both in terms of diagnosing YOD and in providing ongoing support. The panel also agreed that health professionals be aware of the importance of psychosocial support and non-pharmacological interventions to manage neuropsychiatric symptoms. Conclusions The expert panel identified information that they deem essential for health professionals to know about YOD. There was agreement across all thematic categories, indicating the importance of broad professional knowledge related to YOD identification, diagnosis, treatment, and ongoing care. The findings of this study are not only applicable to the delivery of support and care services for people with YOD and their support persons, but also to inform the design of educational resources for health professionals who are not experts in YOD.